Response to Vaccination Against SARS-CoV-2 in Patients With Antineutrophil Cytoplasmic Antibody-Associated Vasculitis With Renal Involvement - Carruthers, Jack E.; Wells, James; Gupta, Arun; Kallon, Delordson; Cox, Amber; Pina, Neuza; Yaqoob, Muhammad Magdi; Rajakariar, Ravindra (Frontiers in Medicine, 2022)
Background Patients with anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitides (AAV) present with multisystem disease including renal impairment. The treatment for AAV involves a high burden of immunosuppression. Patients with renal involvement are treated especially intensively. As a result, we identified these patients as being potentially at high risk of failure to seroconvert to COVID-19 vaccination. Methods We collected data on seroconversion response rates to COVID-19 vaccination in a multi-ethnic cohort of patients with AAV and renal involvement treated at a busy tertiary nephrology centre as part of a retrospective review of patient notes. Blood samples were taken following vaccination with either Pfizer or Astra-Zeneca COVID-19 vaccines and median fluorescence intensity was measured using the validated MULTICOV-Ab Magnetic LuminexⓇ Assay. We also evaluated whether seroconversion was affected by immunosuppression regimen. Results 81 patients were included. The mean age was 62, and there were 49 (60%) females. 55 patients had a blood test after the first dose; 46 after the second dose. Patients were in remission with a median BVAS of 0 (IQR 2). Seroconversion after the first dose with either vaccine was 35/55 (63.6%). After the second it was 38/46 (82.6%). Subgroup analyses revealed a trend to impaired seroconversion in non-white versus white patients (77.8 vs. 81.7% (p = 0.69) after the first dose of vaccine and in those treated with Rituximab in the last 12 months (73.3 vs. 87.1%, p = 0.41). Conclusions These data offer real-world evidence of lower seroconversion in response to vaccination with one dose in patients with AAV and renal involvement than the general UK population. After two doses, seroconversion is in line with national data. These data provide a rationale for hospital-led identification of patients most at risk of COVID-19 and underscore the importance of local connexions between hospitals and their communities. These data provide further support for targeting booster vaccination programmes to vulnerable patient cohorts. They add to the growing evidence of reduced seroconversion in response to vaccination in patients with renal disease of any cause.